Enhancing Security in Discord’s Server: Creating Anti-Spam & Phishing Discord Bots - Azmi, Azri; Abdullah, Dalilah (Journal of Computing Technologies and Creative Content, 2025)
Online communities are increasingly threatened by spam and phishing attacks, compromising user experience and security. This project develops a specialized Discord bot using Python and Discord API to combat these issues. The bot uses Natural Language Processing (NLP) to detect and mitigate spam, including repetitive messages, unsolicited links, and suspicious user behavior. By analyzing message patterns and leveraging community feedback, the bot adapts and evolves its detection capabilities. Rigorous testing across different Discord servers assessed the bot's effectiveness, focusing on detection accuracy, false positive rates, and overall security impact. The results contribute to robust security measures for online communities, particularly on Discord, and offer insights for combating spam and phishing across digital platforms, fostering a safer online ecosystem.